Collaborative Feedback-Based Google Docs as a Digital Authentic Assessment: Students’ Perceptions in Academic Writing - Nadia Eka Putri Indriani; Yenni Rozimela; Syahrul Ramadhan (Darul Yasin Al Sys, 2026)
Digital authentic assessment through collaborative feedback has received increasing attention in academic writing instruction; however, research specifically examining students’ perceptions of Google Docs as a collaborative feedback-based digital authentic assessment medium remains limited. This study aims to analyze students’ perceptions of collaborative feedback-based Google Docs in academic writing assessment. A descriptive quantitative approach supported by qualitative responses was employed using a survey design, involving 41 university students selected through purposive sampling. Data were collected through an online questionnaire consisting of 30 closed-ended items and three open-ended questions. Quantitative data were analyzed using descriptive statistics, including frequency, percentage, mean score, standard deviation, and category interpretation, while open-ended responses were analyzed descriptively through thematic categorization. The findings indicate that students’ overall perception was positive, with a mean score of 3.217. The highest-rated indicator was digital and collaborative feedback, with a mean score of 3.293, which was categorized as very positive. These findings suggest that Google Docs supports feedback delivery, revision, collaboration, and process-based writing assessment in academic writing instruction. This study concludes that collaborative feedback-based Google Docs serves as an effective digital authentic assessment medium for strengthening students’ engagement in the writing process. The study contributes to the development of digital authentic assessment theory and extends current understanding of collaborative feedback practices in academic writing. The findings provide practical implications for lecturers in designing clearer rubrics, structured feedback procedures, and digital literacy guidance to optimize Google Docs-based assessment.